A produção científica em educação musical instrumental dos cursos de música do Ceará - Alves, Sara Sousa (2023)
This work aims to identify and analyze the productions of scientific knowledge (articles) by professors of Instrumental Practice in Music Teaching Courses in Ceará. The interest in this theme arose from the author's experience in research projects and scientific initiation activities. During this involvement with scientific publications, the relevance of Instrumental Music Education (IME) in the formative and reflective process of professionals working in the field of Music became evident. From this perspective, the research has the following starting question: what are the productions of scientific knowledge (articles) elaborated by professors of Instrumental Practice in Music Teaching Courses in Ceará? Therefore, the main objective is to identify and investigate the productions of scientific knowledge (articles) by professors of Instrumental Practice in Undergraduate Music Courses in Ceará. The specific objectives are as follows: a) Evaluate the curriculum structure of Pedagogical Projects of Music Teaching Courses in the state of Ceará; and b) Catalog the research findings and make them available in a database to contribute to the references of professionals working with Music in basic education who use instrumental music teaching practices. The research initially included the analysis of academic texts that provided a brief overview of music education in Brazil, followed by a contextualization regarding IME in the state of Ceará. Additionally, an exploratory research was conducted based on the Pedagogical Projects of higher education courses (PPCs) in Music in Ceará, delimiting the licentiates and the disciplines of Instrumental Practice. The methodological aspects of this study can be characterized as documentary, as it seeks to identify and analyze information that is in a primary state regarding the productions of scientific knowledge (articles) by professors of Instrumental Practice in Music Teaching Courses in Ceará. The results of this analysis highlight the high workload dedicated to the practice of musical instruments and the varied offer of instruments available for the training of teachers in IME in the state of Ceará. However, there is a clear need for further development of scientific production in the field of IME in Ceará, covering all sectors of instrumental practice studies existing in the state.